Effect of multipurpose care solutions upon physical dimensions of silicone hydrogel contact lenses. Issue 5 (26th December 2019) - Smith, Stephanie M.; Zhu, Dongkai; Pierre, David; Gilbert, Jeremy L.; Chinn, Joseph A.
Abstract: Interactions between contact lens multipurpose solution (MPS) components and the contact lenses with which they are used are both lens and solution dependent. As such, lens dimensional changes may arise after cleaning and immersion cycling in different lens care solutions over different time courses. In this study, the dimensional stability of five planned‐replacement silicone hydrogel lenses (lotrafilcon B, comfilcon A, senofilcon A, senofilcon C, and samfilcon A) over 30 cycles in three different MPSs (Biotrue, OPTI‐FREE Express, and OPTI‐FREE Puremoist) was evaluated. Measurements of diameter, sagittal depth, power, roundness, and center thickness were obtained prior to, during, and after 30 cycles of cleaning and storage. Diameters of all lenses increased when soaked in Express or Biotrue but held the International Standards Organization (ISO) tolerance over the full course of 30 disinfection cycles; however, the diameters of comfilcon A, senofilcon A, senofilcon C, and samfilcon A lenses soaked in Puremoist exceeded ISO tolerance after between 4 and 9 immersion cycles. In contrast, the diameter of lotrafilcon B held tolerance. Similarly, all lenses cycled in Express or Biotrue held tolerance for sagittal depth, while in Puremoist only lotrafilcon B held tolerance. All lenses became less round in all MPSs but held tolerance for both power and central thickness. Given the lack of reported clinical issues with Puremoist when used with lenses other than lotrafilcon B, we propose that it may be appropriate to revisit the ISO test methods and tolerances to determine if they are still applicable for silicone hydrogel lenses.